Deindustrialization, economic complexity and exchange rate overvaluation: The case of Brazil (1998-2017) - José Luís Oreiro; Luciano Luiz Manarin; Paulo Gala (PSL Quarterly Review, 2020)
We analyze the determinants of the deindustrialization of the Brazilian economy in the period between 1998 and 2017. This is a typical example of "premature deindustrialization" in the sense that the major reason for the fall in the manufacturing share has not been the increase in per-capita income but rather real exchange rate overvaluation. In the Brazilian case, real exchange rate overvaluation results both from an appreciation of the real effective exchange rate, and an increase in the equilibrium value of the real exchange rate, the "industrial equilibrium exchange rate" of the new developmentalist literature. The elimination of the real exchange rate overvaluation requires not only the adoption of a macroeconomic policy regime in which some kind of real exchange rate targeting is adopted, but also industrial policies designed for increasing the economic complexity of the Brazilian economy and, hence, to reduce the equilibrium value of the real exchange rate.
Keywords: O11; O14; O24; 330; premature deindustrialization; exchange rate overvaluation; Brazilian economy